2016
DOI: 10.1038/srep31279
|View full text |Cite
|
Sign up to set email alerts
|

A whole mitochondria analysis of the Tyrolean Iceman’s leather provides insights into the animal sources of Copper Age clothing

Abstract: The attire of the Tyrolean Iceman, a 5,300-year-old natural mummy from the Ötzal Italian Alps, provides a surviving example of ancient manufacturing technologies. Research into his garments has however, been limited by ambiguity surrounding their source species. Here we present a targeted enrichment and sequencing of full mitochondrial genomes sampled from his clothes and quiver, which elucidates the species of production for nine fragments. Results indicate that the majority of the samples originate from dome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(28 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…Becker et al 2016;Benecke 1994;Greenfield 2014). In recent times, new possibilities for investigating prehistoric sheep have become available, thanks to advances in aDNA analyses (Brandt 2014;Niemi et al 2013;O'Sullivan et al 2016;Olivieri et al 2012;Rannamäe et al 2016a;Rannamäe et al 2016b). We here present and discuss some of the main results from each of these disciplines relating to the study of sheep and sheep fleece.…”
Section: Scientific Approaches To the Study Of Prehistoric Sheep And mentioning
confidence: 99%
See 1 more Smart Citation
“…Becker et al 2016;Benecke 1994;Greenfield 2014). In recent times, new possibilities for investigating prehistoric sheep have become available, thanks to advances in aDNA analyses (Brandt 2014;Niemi et al 2013;O'Sullivan et al 2016;Olivieri et al 2012;Rannamäe et al 2016a;Rannamäe et al 2016b). We here present and discuss some of the main results from each of these disciplines relating to the study of sheep and sheep fleece.…”
Section: Scientific Approaches To the Study Of Prehistoric Sheep And mentioning
confidence: 99%
“…Barber 1991; Bender Jørgensen and Rast-Eicher 2018; Del Freo et al 2010;Frangipane et al 2009), but to our knowledge, there are no published examples of goat hair fibres from the European Bronze Age (Rast-Eicher 2016). Goat skin, however, has been identified in both Neolithic and Chalcolithic contexts (Hollemeyer et al 2012;O'Sullivan et al 2016;Rast-Eicher 2012). Fibre analyses have also demonstrated how fleeces have developed over time (e.g.…”
Section: Textile Archaeology and Fibre Analysismentioning
confidence: 99%
“…By screening sequences against probable sources of preserved leathers, the research team showed that the iceman’s hat came from Brown Bear, his quiver from Roe deer and his loincloth came from sheep 7 . In a similar fashion, FastQ Screen has been used to determine the animal origin of vellum found in 13th century Bibles 8 .…”
Section: Use Casesmentioning
confidence: 99%
“…Finally amongst all these other decisions we must also take into account the original substrate as not all materials have the same biomolecular profile and it might be difficult to obtain specific results for certain materials (outlined in Table 2). We know that obtaining host DNA from tanned skins is often not possible (as the tanning process adversely affects the host nuclear DNA although some mitochondrial DNA may survive [47,48]) so this should be taken into consideration when designing your biocodicological strategy.…”
Section: Q I Am Concerned About the Condition Of A Document Could Tmentioning
confidence: 99%